Assessment of the water quality and microbial regrowth in drinking water treatment plants and the distribution network - Siphelele Nduli; Memory Tekere; Vhahangwele Masindi; Spyros Foteinis (Water Resources and Industry)
Recurring contamination of drinking water and microbial regrowth in distribution networks remains an issue of prime concern to water provision authorities. This is common in the developing world, where aging and under-developed infrastructure along with degraded freshwater resources exacerbate the problem. Here, the year-round measurements, on a weekly basis, of the quality of drinking water from a typical water treatment and distribution system in the South African setting are reported. Results confirmed that the drinking water treatment plants under study rely on heavily degraded freshwater, mainly affected by microbial contamination which could suggest the release of untreated or poorly treated wastewater in receiving water bodies, a common problem in low-and-medium-income countries (LMICs). In most cases, freshwater was effectively treated (e.g., 100% removal for E. coli and over 99%, 92%, and 83% removal for total coliforms, turbidity, and colour, respectively) to meet the drinking water quality standards for South Africa and the world health organisation (WHO) guidelines. Yet, in some monthly measurements, certain contaminants such as ammonia were above the prescribed limits, suggesting the need to operationally improve water treatment and/or curbing the release of untreated or poorly treated wastewater in the catchment. Alarmingly, microbial regrowth was identified within the distribution networks, and this was significantly correlated (p < 0.01) with the distance (from 0 to 101 km) that the water travels within each distribution network and nodes. Also, large seasonal variations in the water quality were observed, with water quality being poorer during winter, likely tracing back to environmental factors in combination with parts of the distribution system being laid proximal to the surface or above ground. Overall, a clear correlation between the chlorine concentration and microbial failure was observed. This could be attributed to high chlorine demand, which devoids the system of residual chlorine, thus, to a larger extent, creating an environment that is conducive to microbial regrowth. Therefore, it can be concluded that high chlorine demand is the main contributor towards microbial regrowth within the water distribution networks, and, as such, comprehensive chlorine demand and decay studies are needed to identify whether chlorine booster stations are required, particularly at the distal ends of the network. This will inform the sustainable top-up of chlorine residual in the distributed water, hence effectively suppressing microbial regrowth. Albeit, high chlorine levels are not a panacea, since these can lead to the formation of toxic and carcinogenic disinfection by-products such as trihalomethanes (THMs). Therefore, first and foremost, focus should be placed on safeguarding the quality of freshwater resources.